Influence of different image‐guided tracking methods upon the local efficacy of CyberKnife treatment in lung tumors. Issue 3 (May 2015) - Guo, Yihang; Zhuang, Hongqing; Zhao, Lujun; Yuan, Zhiyong; Wang, Ping
Abstract: Background: The aim of this study was to explore the influence of image‐guided tumor localization modality (Synchrony tracking vs. Xsight spine‐based localization) on the local efficacy of CyberKnife treatment in lung cancer and lung metastases. Methods: Retrospective analysis of 64 patients with pulmonary metastases and primary tumor cases (72 targets) treated with stereotactic body radiotherapy using CyberKnife was conducted. Synchrony respiratory tracking was used to treat 45 targets, and the remaining 27 targets were treated using Xsight spine (with an extended margin to account for positional uncertainty). The median (80%) isodose line (70–94%) covered the planning target volume at a total dose of 6000 cGy delivered in three fractions. Local efficacy was evaluated by Response Evaluation Criteria in Solid Tumors, accompanied by the follow‐up of local recurrence cases and analysis of tracking methods. Results: Short‐term local control was superior for targets tracked with Synchrony than for targets localized with Xsight spine. There was no statistical difference for targets in the upper lung, but for targets in the lower lung Synchrony tracking was better. Small targets (less than 15 mL) were better controlled when Synchrony was used, but there was no difference for treatment volumes larger than 15 mL. Treatment failures were more likely in the lower lung and for small tumors localized with Xsight spine. Conclusions: The local efficacy of CyberKnife treatment in lung cancer and lung metastases was influenced by image‐guided localization method, target location within the lung, and tumor volume.